2017
DOI: 10.1080/13548506.2017.1417607
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of psychoneuroimmunology-based interventions

Abstract: Psychoneuroimmunology-based interventions are used to attenuated disease progression and/or side effects of pharmacological treatment. This systematic review evaluates the different therapeutic and/or clinical psychoneuroimmunology-based interventions associated to both psychological, neuroendocrine and immunological variables. The review was conducted for all English, Portuguese and Spanish language articles published between 2005 and 2015. Independent investigators analyzed 42 studies concerning human psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 57 publications
1
38
0
1
Order By: Relevance
“…The NK subset was negatively associated with stigma and was positively associated with self-efficacy. The relationship between mental state and immunity has been confirmed by many psychoneuroimmunology studies [ 34 ]. The impact mechanism includes the HPA axis and sympathetic nervous system [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 79%
“…The NK subset was negatively associated with stigma and was positively associated with self-efficacy. The relationship between mental state and immunity has been confirmed by many psychoneuroimmunology studies [ 34 ]. The impact mechanism includes the HPA axis and sympathetic nervous system [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 79%
“…Two 2018 reviews concluded there was an overall pattern of pro-inflammatory downregulation with the practice of yoga [23,24]. As mentioned, only one yoga study to date has measured inflammatory markers in participants with chronic pain [22].…”
Section: Discussionmentioning
confidence: 99%
“…arthritis, irritable bowel disease) and inflammation has been linked to other chronic pain conditions, such as low back pain [22]. Existing studies have highlighted the association between yoga practice and reduced inflammation [23,24]; however, only one study to date has focused on participants with chronic pain [22]. In that 12-week non-randomized study, TNF-alpha (pro-inflammatory marker) remained unchanged in the intervention group but increased significantly in the control group.…”
Section: Introductionmentioning
confidence: 99%
“…There are many forms of meditation that use various different techniques, but overall, meditation seems to reduce blood cortisol, CRP, TNF-α, IL-6, and the activity of the transcription factor NF-κB in a number of different types of meditation practices. 80 , 88 90 In addition, a recent meta-analysis found that MBIs that included breathing, meditation, yoga, and Tai Chi downregulated pro-inflammatory genes and pathways and identified the NF-κB pathway as being consistently downregulated. The authors concluded that “the various psychological and physiological benefits of MBIs may be mediated through the downregulation of proinflammatory genes and pathways.” 91 …”
Section: Nonpharmacologic Interventions That Lower Pro-inflammatory Mmentioning
confidence: 99%